Coesão e coerência textuais sob a perspectiva da teoria da argumentação na língua - Aldrovandi, Makeli (2014)
It has been proposed, by this work, the explanation of the phenomena cohesion and coherence, coined by Textual Linguistics, under the light of the Theory of Argumentation within Language (AWL), developed by Oswald Ducrot and fellow researchers. We have justified the research for there is a need to explain the construction of the meaning in a discourse by the means offered by Language itself, since it underlies all discourses, it is within it that speakers search the elements to enunciate, and it is through it that they enunciate. This is the differential of Argumentation Theory within Language: analyzing utterances and discourses starting from the Language. To this Theory, language is fundamentally argumentative. Thus, any choice of the speaker influences the meaning built by him. The meanings, according to Theory of Semantic Blocks (TSB) - current phase of AWL - can be explained by means of argumentative chaining. The discourses analyzed are chronicles, and the application of the concepts of TSB has allowed us to describe how cohesion and coherence can be explained in terms of AWL. By raising the internal and external argumentations of the lexicon and utterances and by the relationships established between the semantic blocks and argumentative aspects of the same semantic block in the discourses analyzed, it has been possible to cast a particular view on the long known phenomena which are cohesion and coherence.